WHY THE VAULT BECAME SUPERIOR TO OTHER EVENTS IN WOMEN'S ARTISTIC GYMNASTICS AT THE OLYMPICS? - Jun He; Jeffrey Montez de Oca; Lei Zhang (University of Ljubljana Press (Založba Univerze v Ljubljani), 2022)
Critics argue that disciplines in women's artistic gymnastics are not equal and the vault is generally scored much higher than the uneven bars, balance beam and floor exercise. The aim of this study is to understand why the vault became superior to other women's events. The data are the official results for the 586 women gymnasts in Qualification at Olympics from 2000 to 2020. The One-Way ANOVA was used to analyze the variance of D-scores, E-scores and F-scores for women gymnasts obtained on each apparatus. Our research shows that disciplines in women's artistic gymnastics have not been equal for gymnasts when trying to obtain high F-scores in the past 6 Olympics. Among the four women's events, the vault came to be the one on which gymnasts are more likely to obtain high F-scores after the 2000 Olympics. We indicate that the strength of vault resulted from the introduction of the new vaulting table in 2001 and the new open-ended rules in 2006. Although the two big changes implemented by the International Federation of Gymnastics in the beginning of the new millennium were aimed at improving safety of the vault and fairness of judging, the interplay of the two big changes unintentionally promoted the vault to become the most powerful event in women's artistic gymnastics. Such unanticipated consequence of purposeful action may constitute the most important element (i.e., imbalance of disciplines) in the sport. Accordingly, this research has the potential to shed new light on not only this important topic of equality between disciplines, but also broader trends in modern artistic gymnastics.